Human macrophage response to the emerging enteric pathogen Aeromonas veronii: Inflammation, apoptosis, and downregulation of histones - Nicholas Naidovski; Sarah K. T. Chong; Fang Liu; Stephen M. Riordan; Michael C. Wehrhahn; Christopher Yuwono; Li Zhang (Virulence)
This study investigated the pathogenic mechanisms of Aeromonas veronii in macrophages. THP-1 derived macrophages were used as a human macrophage model and were treated with A. veronii strain AS1 isolated from intestinal biopsies of an IBD patient, or Escherichia coli strain K-12. RNA was extracted and subjected to RNA sequencing and comparative transcriptomic analyses. Protein levels of IL-8, IL-1β, IL-18, and TNFα were measured using ELISA, and apoptosis was assessed using caspase 3/7 assays. Both A. veronii AS1 and E. coli K-12 significantly upregulated the expression of many genes involving inflammation. At the protein level, A. veronii AS1 induced significantly higher levels of IL-8, TNFα, mature IL-18 and IL-1β than E. coli K-12, and led to greater elevation of caspase 3/7 activities. Both A. veronii AS1 and E. coli K-12 upregulated the expression of CASP5, but not other caspase genes. A. veronii AS1 significantly downregulated the expression of 20 genes encoding histone proteins that E. coli K-12 did not. The more profound pathogenic effects of A. veronii in inducing inflammation and apoptosis in macrophages than E. coli K-12 are consistent with its role as a human enteric pathogen. The upregulated expression of CASP5 and increased release of IL-1β and IL-18 support the role of CASP5 in activation of non-canonical inflammasome. The downregulation of histone genes by A. veronii suggests a unique impact on host cell gene expression, which may represent a novel virulence strategy. These findings advance the understanding of pathogenic mechanisms of the emerging human enteric pathogen A. veronii.